The Field Measurement of Fundamental Period of Buildings in Thailand by Using HVSR Method - Tha Toe, Tun Tun; Ornthammarath, Teraphan (การประชุมวิศวกรรมโยธาแห่งชาติ ครั้งที่ 28, 2023)
Seismicity of Bangkok is different with other cities as it is situated on the low seismic zone but placed on the border of the Indo-Australian and Eurasian plates which can produce the large earthquake. Evaluation of fundamental period by using ambient vibration data is the frequently used method. A group of the existing reinforced concrete buildings, height range from 17 m to 124 m, situated in the Bangkok City; Thailand have performed the ambient vibration test and HVSR method will be used to compute the fundamental frequencies and fundamental periods of the buildings in this paper. A numerical analysis developing the finite element technique (FEM) will be done to verify the accuracy of the measurement results. FEM has also been used to assess the impact of infill wall stiffness and infill wall opening percentage on the fundamental period and higher modes of RC frame constructions.